Komunikasi Pemasaran Kennedy, Voice & Berliner dalam Membangun Loyalitas dengan Klien - Jacqueline Annabell; Yugih Setyanto; Sisca Aulia (Prologia, 2019)
Marketing communication is carried out with the main goal of selling. Companies that offer services and products compete with each other in applying marketing communication strategies to attract clients and maintain the loyalty of clients who have become regular customers. This research utilizes marketing communication theory and client's loyalty. The research approach used in this research is a descriptive qualitative approach with case study research methods and data collection techniques carried out by interviews, non-participant observation, literature study and documentation. The result of this study indicates that Kennedy, Voice & Berliner runs a mix of marketing communications, namely events and experiences, public relations and publicity, direct marketing, word-of-mouth marketing, and personal selling. Kennedy, Voice & Berliner clients have a high level of engagement and are supported by a high level of repeated purchase, reciprocity and client's satisfaction with Kennedy, Voice & Berliner in which they use the services of Kennedy, Voice & Berliner’s  public relations consultant on an ongoing basis. Komunikasi pemasaran dilaksanakan dengan tujuan utama menjual. Perusahaan-perusahaan yang menawarkan jasa maupun produk saling berkompetisi dalam mengaplikasikan strategi komunikasi pemasaran untuk menarik minat klien serta mempertahankan loyalitas klien yang telah menjadi pelanggan tetap. Penelitian ini menggunakan teori komunikasi pemasaran dan loyalitas klien. Pendekatan penelitian yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskriptif dengan metode penelitian studi kasus dan teknik pengumpulan data dilakukan dengan wawancara, observasi non-participant, studi pustaka dan dokumentasi. Hasil penelitian ini menunjukan bahwa Kennedy, Voice & Berliner menjalankan bauran komunikasi pemasaran yaitu events and experiences, public relations and publicity, direct marketing, word-of-mouth marketing, dan personal selling. Klien Kennedy, Voice & Berliner memiliki keterikatan yang tinggi dan didukung dengan  tingkat pembelian ulang yang tinggi, adanya timbal balik dan rasa puas klien terhadap Kennedy, Voice & Berliner sehingga memakai jasa konsultan public relations Kennedy, Voice & Berliner secara terus-menerus.